Editorial (@limentech, Ciencia y Tecnología Alimentaria, 2023)
The Journal @limentech, Food Science and Technology presents its volume 21, number 2 of 2023, focused on sharing the results of research carried out by young researchers from different institutions of higher education and SENA. This effort is part of the Meeting of Research Semilleros of Food Engineering programs and related areas (ENSIAL), organized by students and teachers of the Food Engineering program of Villa del Rosario, Norte de Santander, Colombia.The articles cover topics relevant to the agri-food sector, including biotechnology and food technology, reflecting advances and trends in the field. The motivation and participation of the seedbed researchers, both nationally and internationally, in the dissemination of their findings is highlighted.We invite you to continue researching and publishing in the journal, and thank the scientific committee and reviewers for their commitment to the scientific community in the area of Food Science and Technology.For more information, visit the journal's website: Revista @limentech.